Arginase Inhibitor 2,3,5,4′-Tetrahydroxystilbene-2-O-β-D-Glucoside Activates Endothelial Nitric Oxide Synthase and Improves Vascular Function - Yi, Bonggu; Nguyen, Minh Cong; Won, Moo-Ho; Kim, Young Myeong; Ryoo, Sungwoo (Planta Medica, 2017)
Endothelial arginase constrains the activity of endothelial nitric oxide synthase by reducing nitric oxide bioavailability, which contributes to vascular diseases. During screening, we identified a novel compound from the rhizome of Polygonum multiflorum (Polygonaceae), 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucoside (THSG), which inhibited arginase activity. THSG exhibited noncompetitive inhibition of arginase II and inhibited both arginases I and II in a dose-dependent manner. THSG-dependent arginase inhibition reciprocally increased nitric oxide production and decreased reactive oxygen species generation in aortic endothelia. These effects were associated with increased dimerization of endothelial nitric oxide synthase without changes in the protein expression levels of arginase I, arginase II, or endothelial nitric oxide synthase. In vascular tension assays, when aortic vessels from wild-type mice are incubated with THSG, responses to the nitric oxide-dependent vasorelaxant acetylcholine were augmented, but responses to an nitric oxide donor, sodium nitroprusside, were not affected. On the other hand, phenylephrine-dependent vasoconstriction was significantly retarded in THSG-treated vessels. In a high-cholesterol diet-fed atherogenic model mice (ApoE-/-), THSG improved endothelial function by enhancement of the nitric oxide-cGMP pathway. Taken together, these results suggest that THSG may exert vasoprotective effects through augmentation of nitric oxide signaling by inhibiting arginase. Therefore, THSG may be useful in the treatment of vascular diseases that are derived from endothelial dysfunction, such as atherosclerosis.
Keywords: Polygonum multiflorum; Polygonaceae; 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucoside; arginase; endothelial nitric oxide synthase; superoxide; vascular function